MENIMBANG POLIGAMI DALAM HUKUM PERKAWINAN - Ali Imron (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Marriage is essentially a reunification of men and women consisting of elements of soul and body are fused into one in a household frame for emotional and physical welfare. Regulation of marriage embraced the principle that a man may only have a wife and vice versa. The court may grant permission to the husband to a wife more than a certain requirements. Qualitative and quantitative Justice as a condition of polygamy difficult and even impossible to be realized. Polygamy is synonymous with the exploitation of women for the sake of greed and sexual lust. Key words: Marriage, Polygamy, Islamic Law